Student Participation as a Reflection of the Teacher’s Knowledge, Skills, and Values - Swaran Singh, Charanjit Kaur; Tunku Mohtar, Tunku Mohani; Masa Singh, Tarsame Singh; Eng Tek, Ong; Md Yunus, Melor (International Journal of Psychosocial Rehabilitation, 2019)
Student participation poses a challenging factor in the teaching and learning dimension. However, its importance in reflecting the teacher’s professionalism is hardly understood or simply taken for granted. This perception could be attributed to the lack of clarity of the concept of student participation. Various studies have defined it in different ways. This paper examines the multifarious concepts of student participation. The benefits of student participation and the factors which inhibit student participation are highlighted the concept of student participation that is adopted is discussed in relation to the teacher’s knowldge, skills, and values.